2019
DOI: 10.1007/s11082-019-1960-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced numerical design of two-barrier infrared detectors with III–V compounds heterostructures considering the influence of lattice strain and misfit dislocations on the band gap

Abstract: The goal of this work is the design of efficient infrared radiation detectors based on InAsSb compounds with two energy barriers around the absorber region. Two types of two-barrier detectors that work in the 3-5.5 μm wavelength range at 230 K is designed. Using our computer program to iteratively solve the Poisson equation, the spatial distribution of energy band edges in III-V heterostructures was calculated The influence of lattice stress, bending of the structure and doping on the energy shift of the edge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…InAs/GaSb SLs are more explored than InAs/InAsSb in terms of their physical properties, but it has been reported that introducing gallium atoms to the structure lowers the structural quality of the material through native point defects and has a negative impact on working parameters of the device 25 . To balance the gallium-induced defects it is crucial to maintain a balanced strain throughout the whole growth process to avoid "relieving" the strain by the SL through formation of the defects 26 .…”
Section: Introductionmentioning
confidence: 99%
“…InAs/GaSb SLs are more explored than InAs/InAsSb in terms of their physical properties, but it has been reported that introducing gallium atoms to the structure lowers the structural quality of the material through native point defects and has a negative impact on working parameters of the device 25 . To balance the gallium-induced defects it is crucial to maintain a balanced strain throughout the whole growth process to avoid "relieving" the strain by the SL through formation of the defects 26 .…”
Section: Introductionmentioning
confidence: 99%